Differential Expression of Genes Involved in Saikosaponin Biosynthesis Between Bupleurum chinense DC. and Bupleurum scorzonerifolium Willd - Yu, Ma; Chen, Hua; Liu, Shi-Hang; Li, Yu-Chan; Sui, Chun; Hou, Da-Bin; Wei, Jian-He (Frontiers in Genetics, 2020)
Radix Bupleuri (roots of Bupleurum spp.) is an important medicinal herb. Triterpenoid saponins of saikosaponins generally constitute the main class of secondary metabolites of plants in the Bupleurum genus. However, the molecular regulatory mechanism underlying their biosynthesis remains elusive. In this study, we observed significantly different saikosaponin biosynthesis between Bupleurum chinense and Bupleurum scorzonerifolium at the seedling stage. The sequential and expression characterization of 232 genes in the triterpenoid saponin biosynthetic pathway, which includes the mevalonate (MVA) pathway and methylerythritol phosphate (MEP) pathway, between B. chinense and B. scorzonerifolium was also investigated. Sixty of these genes may be involved in saikosaponin biosynthesis. Manipulation of these genes, especially those of the β-AS, P450, and UGT families, may improve saikosaponin production.